2008
DOI: 10.1007/s10350-008-9225-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients on Renal Replacement Therapy after Colorectal Surgery

Abstract: Renal patients have a high rate of complications after colorectal surgery, and emergency surgery has a significant risk of anastomotic leak. Primary anastomosis should be avoided in all patients undergoing emergency intestinal resections. Subsequent surgery to restore intestinal continuity is possible in 90 percent of patients with far fewer complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…The authors also stated that mortality was 5% after elective surgery and 26% for emergency cases. 29 However, these percentages for control patients without end-stage renal disease were not presented in the article similarly to most other reports. [16][17][18][19]21,22,28 As far as we know, the current study is the first cohort review comparing the frequency of complications and oncological outcomes after surgical resection for CRC between distinct CKD stages.…”
Section: Discussionmentioning
confidence: 52%
“…The authors also stated that mortality was 5% after elective surgery and 26% for emergency cases. 29 However, these percentages for control patients without end-stage renal disease were not presented in the article similarly to most other reports. [16][17][18][19]21,22,28 As far as we know, the current study is the first cohort review comparing the frequency of complications and oncological outcomes after surgical resection for CRC between distinct CKD stages.…”
Section: Discussionmentioning
confidence: 52%
“…A 1%-3% risk of anastomotic failures requiring "rescue colostomy" persists in elective surgery. 36,37 In contrast, in terms of comparable risks in elective surgery, Krysa and colleagues 38 showed that emergency colorectal surgery in patients who received renal replacement therapy resulted in an 81% overall complication rate, mortality of 26% and a substantial anastomotic leakage rate of 71% for primary anastomosis. Our study confirms the increased anastomotic leakage rate after emergency operations and suggests performing a protective loop ileostomy in case of colorectostomy.…”
Section: Discussionmentioning
confidence: 99%
“…43 In a meta-analysis of various non-cardiac surgeries, patients with chronic renal disease are at 2-to 5-fold higher risk for postoperative death and cardiovascular events than those with normal renal function. 44 Postoperative morbidity after elective orthopaedic surgery is also higher in patients with chronic renal disease.…”
Section: Discussionmentioning
confidence: 99%